The multicampus system the U.P. experience - Rola, Dionisia A. (Philippine Journal of Public Administration, 1983)
The adoption of the multicampus system for UP, as part of its process of growth, is inevitable. There has been a strengthening of the regional units in response to expressed aspirations, regional/local needs and national priorities. Specialization, diversity and cooperation characterize the UP's multicampus network. Direct outcomes of this sytem have been: (1) greater educational opportunities for middle and lower income groups via the non-Metro Manila campuses; (2) increase in collaborative research and action projects with other agencies, including joint planning efforts toward project adoption and implementation; and (3) development of cultural awareness because of cultural activities and research initiated by the regional units. Throughout the multicampus experience, the UP has not lost sight of its mission to reach out to more Filipinos beyond the elite and urban population through relevant quality instructional, research and extension programs.